Omega-3 polyunsaturated fatty acids and brain aging. Issue 2 (March 2015) - Denis, Isabelle; Potier, Brigitte; Heberden, Christine; Vancassel, Sylvie
Abstract : Purpose of review: The literature on the influence of dietary omega-3 polyunsaturated fatty acid (ω-3 PUFA) on brain aging has grown exponentially during the last decade. Many avenues have been explored but no global picture or clear evidence has emerged. Experimental studies have shown that ω-3 PUFA is involved in many neurobiological processes that are involved in neurotransmission and neuroprotection, indicating that these PUFAs may prevent age-related brain damage. Human studies have revealed only a weak link between ω-3 PUFA status and cognitive aging, whereas interventional studies have yet to confirm it. The purpose of this review is to analyze the developments in the area during the last 2 years. Recent findings: Human brain MRI studies have confirmed previous findings that ω-3 PUFA can protect the brain during aging; two intervention studies obtained clear evidence. We also analyzed the experimental data clarifying the involvement of ω-3 PUFA in neurotransmission, neuroprotection (including prevention of peroxidation, inflammation, and excitotoxicity), and neurogenesis, thereby helping the brain cope with aging. Summary: These recent human and experimental studies provide support for and clarification of how ω-3 PUFA protect against brain aging and highlight the main lines for future research.